Competitive Team-Based Learning Vs. Student Teams-Achievement Divisions in a Reading Class - Akbarzadeh, Mojtaba; Hosseini, Seyed Mohammad Hassan (Center of Language and Cultural Studies [CLCS], 2021)
This study, which was conducted as part of the final thesis in the master’s degree program in English didactics, attempted to measure the effects of Competitive Team-Based Learning (CTBL), developed by Hosseini (2000, 2020 & 2021) at Mashhad Education Office in Iran, vis-à-vis Student Teams-Achievement Divisions (STAD), developed by Slavin and associates (1977) at Johns Hopkins University in the U.S., on the reading comprehension of Iranian EFL intermediate students. As an emerging innovative Cooperative Learning (CL) oriented approach, CTBL accentuates systematic implementation of teamwork in competitive environments with a democratic ambiance. The findings of some researchers on the effectiveness of this revolutionary approach to language teaching/Education have been brought to the fore for the benefit of those interested. Sixty students were selected out of 75 based on their scores in a PET reading test. Then they were randomly assigned to two groups: control and experimental. Each group consisted of thirty participants, which were divided into seven teams of four – the two remained students in each class worked in pairs. While the control group was instructed via STAD method of CL, the experimental group was instructed via Hosseini's approach to (language) teaching (i.e., CTBL). The reading comprehension test (posttest) was used at the end of the study to assess the probable progress in the reading comprehension ability of the students. The results on an independent T-test showed statistical significance at P≤0.05 level that can be attributed to the effect of CTBL on the participants' reading comprehension achievement. Probable reasons for the success of CTBL have been elaborated at length. Implications of the study as well as some suggestions to language teachers, syllabus designers, methodologies, and researchers have also found a place at the end of this paper.